Actualización, Clinica Diagnostica y Terapeutica de la Nefritis Lupica - Alvaro Rios, Diego Alexander (2023)
ABSTRACT: Lupus nephritis is considered glomerulonephritis, one of the most common complications of systemic lupus erythematosus, affecting between 40 and 70% of patients. Its prevalence in adults is 25-159 cases per 100,000 inhabitants, while in pediatric patients, this incidence is 0.76 per 100,000 inhabitants each year. A descriptive, cross-sectional cohort study was carried out, in which information regarding the subject of different scientific articles and bibliographic material that have been published during the period 2018-2023 was analyzed, where the characteristics of the disease were identified, as well as the clinical implications of this in daily life. As the main results, it was obtained that lupus nephritis, being a complication of systemic lupus erythematosus, prevalently affects female patients in a ratio of 9 to 1 concerning males; it also has a high prevalence in people of black, Hispanic, and Asiatic, in which it showed a more aggressive evolution, with increased rates of renal replacement therapy. The diagnosis of LN is based on several criteria, such as proteinuria and hematuria, manifestations present in the majority of cases; even so, the gold standard is the percutaneous renal biopsy, which allows identifying the histological variant of the disease and determining the most helpful treatment according to the findings of said study. Since SLE and LN are autoimmune diseases with variable clinical characteristics, they are a medical challenge in terms of their diagnosis, which must be timely, which, together with adequate treatment, aims to avoid exacerbations, control symptoms, and improve the quality of life of patients, promoting a healthy lifestyle, maintaining the integrity of organs, devices, and systems, with a focus on kidney health. Keywords: Systemic lupus erythematosus, lupus nephritis, glomerulonephritis, chronic renal failure, autoimmune disease.